Effect of melanin isolated from antarctic yeasts on preservation of pig livestock after ablactation - Chyizhanska, N.; Beregova, T. (Ukrainian Antarctic Journal, 2009)
Particularly high mortality rate among pigs observed after weaning. The main reason for this phenomenon is the stressful situation. One of the most promising way to prevent the consequences of stress at weaning and aimed to increase the overall resistance of the organism of piglets is the use of biologically active substances in diets. Our data and data of others on the anti-stress effect of melanin were basis for experiments on the use of melanin in the agricultural facilities that specialized in growing pigs. We found that the addition of melanin to piglets’ diet during weaning completely abrogated their illness and mortality.